UMA ESCUTA NECESSÁRIA: A DOR DA FOME EM (DIS)CURSO NO PODCAST “ENTRE VOZES” - SILVA, ALINE APARECIDA DA (2023)
Hunger is a social problem that puts the survival´s human species at stake and has been taking shelter in Brazilian homes as a permanent scourge. The increased number of people who suffer from hunger in Brazil has brought to light already forgotten campaigns, which highlighted the ills arising from the lack of food in the national territory in recent years. Given this panorama, the main objective of this research is to investigate how the meanings about hunger are produced in the podcast episode entitled “Among Voices: the ghost of hunger returns to haunt Brazil”, produced by CNN Brazil, thinking about the discursive podcast functioning, which circulates in the digital space, through streaming platforms, from 2021. The research question that mobilizes us is: how the speeches about hunger have been produced in the podcast analyzed? As specific objectives, we list: a) understand the podcast as one of the new information and communication technologies that has been affecting the way the subject relates to the world and to the other; b) investigate which discursive formations intersect the journalistic discourse on hunger, as well as which effects of meaning; c) analyze the voice, in podcasts, as a process of subjectivation of the subject and as a unique event, which is not repeated (SOUZA, 2018). The theoretical-methodological support on which the research is based is the Franco-Brazilian Discourse Analysis, having as main references Michel Pêcheux (1997, 2014 and 2015), Eni Orlandi (2007, 2004), Pedro de Souza (2018) and Dias (2011; 2016; 2018). After the analytical movement, we can say that, due to the lack of public policies, hunger is a social problem and that it is a digital discursive space. Thus, the digital space modifies the urban space as much as the urban space is able to mark the digital space.